Reading outcomes in children with developmental language disorder: A person-centered approach. (December 2020) - Erisman, Marja C; Blom, Elma
Background and aims: Many children with Developmental Language Disorder (DLD) develop reading difficulties. The purpose of this study is to better understand variation in the reading outcomes of children with DLD using a person-centered approach. Method: 87 monolingual Dutch children diagnosed with DLD performed at ages 5 or 6 years nine tests of nonverbal IQ, oral language proficiency, phonological memory (PM) and executive functioning (EF). Two years later, the same children were tested on single (non-)word reading. Latent profile analyses were conducted to identify profiles based on oral language proficiency, phonological memory and executive functioning at age 5–6 years, which, in turn, were related to nonverbal IQ and to single-word reading two years later. Results: Four profiles were identified and labelled relative to their position within the DLD-sample: 1. Weak performance overall, 2. Strong EF-average language and PM, 3. Mild working memory (WM) deficiencies-average language and PM, 4. Strong development overall. Profiles 1 and 3 had below average nonverbal IQ scores and were associated with low word reading outcomes two years later. Conclusions: Within the group of children with DLD, children with relatively weak oral language, phonological memory and executive functioning, or children with working memory deficiencies are most at risk for developing reading difficulties. The findings support a multiple risk framework and confirm that a person-centered approach is promising in predicting reading outcomes in DLD. Implications: Research into individual differences in DLD is dominated by variable-centered approaches. This study illustrates how a person-centered approach, which views variables as properties of individuals, captures variation in the DLD-population. Using this bottom-up approach, the study highlights how an individual's strengths and weaknesses across different developmental domains can be combined into profiles that relate to later reading outcomes. As such, it can provide an example for future DLD research.